Synthesis and Characterization of ZIF-67 Mixed Matrix Nanobiocatalysis for CO2 Adsorption Performance - Saeed, Saira; Bashir, Rashdia; Rehman, Shafique Ur; Nazir, M. Tariq; ALOthman, Zeid A.; Muteb Aljuwayid, Ahmed; Abid, Amin; Adnan, Ahmad (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, ZIF-67 based mixed matrix membrane was synthesized with solution casting method using tetrahydrofuran as solvent. The as-synthesized ZIF-67 was characterized using PXRD, TGA, ATR-FTIR and BET analysis for the surface area measurements. The minimum 3wt% loading of ZIF-67 was incorporated within hydrophobic polymer to evaluate CO2 adsorption performance of ZIF-67. The stability of ZIF-67 in pure water and inorganic solvents was investigated. The maximum CO2 adsorption of ZIF-67 mixed matrix membrane (MMM) was 0.5mmol/g at 273K is higher than pure polymer. The fabricated ZIF-67 based mixed matrix membrane showed higher CO2 capture even at lower MOF loading using THF. The current study highly recommends the combination of hydrophobic polysulfone and a water stable ZIF-67 for CO2 capture from wet flue gases.